2021
DOI: 10.12912/27197050/137863
|View full text |Cite
|
Sign up to set email alerts
|

Sewage Sludge as a Component to Create a Substrate for Biological Reclamation

Abstract: The main ways of sewage sludge disposal in the European Union and Ukraine were considered. The main problems of sludge utilization in Ukraine were identified. Research on the possibility of using a substrate based on sewage sludge for biological reclamation of disturbed lands was conducted. The quality of the sludge from Lviv WWTP was determined. The best substrate composition for biological land reclamation was determined by using bioindication. It was established that the use of settled sludge observed inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
3
0
1
Order By: Relevance
“…Tymchuk et al (2021) confirms the positive effect of adding natural sorbents to the composition of the substrate and notes that there are noticeable positive changes in the growth and development of plants.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Tymchuk et al (2021) confirms the positive effect of adding natural sorbents to the composition of the substrate and notes that there are noticeable positive changes in the growth and development of plants.…”
supporting
confidence: 66%
“…Sludge can be considered as a substrate for fertilization and soil recultivation, as they are a source of significant concentrations of macro-and micronutrients in particular nitrogen, phosphorus, potassium which are considered as components of organo-mineral fertilizers of different composition and purpose to improve soil quality (Paya et al, 2018;Zhu et al, 2004;Tymchuk et al, 2021;Tymchuk et al, 2022). However, SS tends to accumulate heavy metals (Wu et al, 2015;Hei et al, 2016) and organic pollutants (Clarke & Smith, 2011), pharmaceuticals (Khan et al, 2021;Boillot et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…To perform soil reclamation in one application, different combinations of sewage sludge, mineral wool, post-flotation lime, and mineral fertilisers were introduced into degraded soil. Furthermore, the publication of Tymchuk et al (2021) identified the main problems of the disposal of wastewater in Ukraine. The research discussed the possibility of using a sewage sludge-based substrate for the biological reclamation of affected areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of these unconventional energy sources is drainage water discharged from flooded areas. The problem of drainage water treatment is related to its purification from contaminants: ammonium ions (Malyovanyy et al, 2013;Sakalova et al, 2019), phosphates (Tulaydan et al, 2017;Tymchuk et al, 2020;Tymchuk et al, 2021), heavy metals (Kostenko et al, 2017) and their use as non-traditional energy sources.…”
Section: Introductionmentioning
confidence: 99%